Greece: Light at the end of the tunnel - Jens Bastian (Stiftung Wissenschaft und Politik (SWP), 2014)
Where does Greece stand today, six years after the outbreak of a severe economic crisis, which has led to drastic social repercussions and contributed to major political changes in the country? Key questions are being asked in public debates: If Greece requires a third rescue programme, what compliance requirements should be included, and how would such a programme be financed? (SWP Comments)
Keywords: 320